Delirium and Cognitive Screening in National Hip Fracture Registries: Scoping Review Protocol [version 2; peer review: 2 approved] - Pamela Hickey; Rose S. Penfold; Louise Brent; Niamh A. Merriman; Eithne Sexton; Tara Coughlan; Mary E. Walsh; Antony Johansen; Catherine Blake; Alasdair M. J. MacLullich; Andrew J. Hall; Cristina Ojeda-Thies (HRB Open Research, 2025)
Background Delirium and cognitive impairment are common in hip fracture populations and are associated with significant adverse patient outcomes. National hip fracture registries facilitate improvements in patient outcomes and care quality, such as reduced mortality and the development of specialist multidisciplinary services. However, there is substantial variation in the data collected and reported in relation to delirium and cognition, which impedes international comparison and may reduce quality of care. Objective This scoping review aims to identify delirium and cognition data items currently collected by hip fracture registries internationally, to identify associated registry guidance that exists for the administration of delirium and cognitive screening tools, and report outcomes of these data items across the most recently published annual reports of identified hip fracture registries. Methods This scoping review will be conducted in accordance with the Preferred Reporting Items for Systematic Reviews extension for Scoping Reviews (PRISMA-ScR). We will search the following databases: Medline Ovid; Embase; CINAHL EBSCOHost. Relevant websites such as the Fragility Fracture Network (FFN) will also be searched. Study selection and review will be carried out independently by two research team members, with discrepancies resolved by a third member of the research team. Data extraction and synthesis will be conducted by one reviewer and checked for accuracy and omissions by another. The scoping review findings will be informed and validated through engagement with the FFN Hip Fracture Audit Special Interest Group, who will share their knowledge, expertise, and research to achieve consensus over core aspects of the scoping review findings. Conclusion By identifying existing heterogeneity in delirium and cognitive screening tool use and administration, it is hoped that administration and specific screening tool use will become standardised to optimise comparability across countries and ensure that high quality and reliable data are included across international registry reports.